Kajian Literatur: Faktor yang Mempengaruhi Konsumsi Alkohol dan Dampak Alkohol Terhadap Kesehatan Berdasarkan Teori Perilaku - Lutfia Nafisatul Hanifah (Media Gizi Kesmas, 2023)
Background: Human health conditions are not only physically health, but also mentally health. Consuming alcoholic beverages in excess can leads to addiction. Many cases of crime are caused by excessive alcohol consumption. Alcohol addiction can also lead to chronic diseases such as heart disease, liver cirrhosis and cancer. The mortality rate caused by alcohol consumption has a high percentage of death cases worldwide. Objectives: The objective of the study is to determine the factors that influence alcohol consumption and the health effects that will arise if someone consumes alcoholic beverages in excess. Methods: The method used was literature review with 6 journals based on the topic. Results: Lack of knowledge and understanding on policies related to alcoholic beverages made people who consume alcohol ignore the impacts that appear and coupled with a lack of support from the surrounding environment makes someone become an alcoholic and take on outside of self-control. Conclusions: Alcoholics can experience the health problems such as organic mental health disorders (GMO) which can lead to negative thoughts, increased emotions, and so on. So that it can lead to the emergence of crimes ranging from acts of physical and verbal violence, sexual harassment to murder.